Efficacy and Safety of Albumin-Bound Paclitaxel Compared to Docetaxel as Neoadjuvant Chemotherapy for HER2-Negative Breast Cancer - Lv, Zhi-Dong; Song, Hong-Ming; Niu, Zhao-He; Nie, Gang; Zheng, Shuai; Xu, Ying-Ying; Gong, Wei; Wang, Hai-Bo (Frontiers in Oncology, 2022)
Background Nanoparticle albumin-bound paclitaxel (nab-paclitaxel) as neoadjuvant chemotherapy (NAC) for breast cancer remains controversial. We conducted a retrospective study to compare the efficacy and safety of nab-paclitaxel with those of docetaxel as neoadjuvant regimens for HER2-negative breast cancer. Methods In this retrospective analysis, a total of 159 HER2-negative breast cancer patients who had undergone operation after NAC were consecutively analyzed from May 2016 to April 2018. Patients were classified into the nab-paclitaxel group (n = 79, nab-paclitaxel 260 mg/m2, epirubicin 75 mg/m2, and cyclophosphamide 500 mg/m2) and the docetaxel group (n = 80, docetaxel 75 mg/m2, epirubicin 75 mg/m2, and cyclophosphamide 500 mg/m2) according to the drug they received for neoadjuvant treatment. The efficacy and adverse events were evaluated in the two groups. Results The pathological complete response (pCR)(ypT0/isN0) rate was significantly higher in the nab-paclitaxel group than in the docetaxel group (36.71% vs 20.00%; P = 0.031). The multivariate analysis revealed that therapeutic drugs, lymph node status, and tumor subtype were the most significant factor influencing treatment outcome. At a median follow-up of 47 months, disease-free survival (DFS) was not significantly different in those assigned to nab-paclitaxel compared with docetaxel (82.28% vs 76.25%; P = 0.331). The incidence of peripheral sensory neuropathy in the nab-paclitaxel group was higher than that in the docetaxel group (60.76% vs 36.25%; P = 0.008), while the incidence of arthralgia was observed more frequently in the docetaxel group (57.50% vs 39.97%; P = 0.047). Conclusions Compared with docetaxel, nab-paclitaxel achieved a higher pCR rate, especially those patients with triple-negative breast cancer or lymph node negative breast cancer. However, there was no significant difference in DFS between the two groups. This study provides a valuable reference for the management of patients with HER2-negative breast cancer.